The Effect of Good Corporate Governance on Tax Avoidance - Maulidah Nabilah; Umaimah Umaimah (Indonesian Vocational Research Journal, 2022)
This study aims to prove the effect of good corporate governance as proxied through independent commissioners, institutional ownership and audit committees on tax avoidance practices by manufacturing companies listed on the Bursa Efek Indonesia in 2019-2020. The independent variables used are independent commissioners which are measured by comparing the number of independent commissioners and the total number of boards of commissioners, then institutional ownership which is measured by comparing the number of shares owned by the institution with the number of shares outstanding, and the audit committee as measured by the number of audit committees. The dependent variable used is tax avoidance which is measured using the Effective Tax Rate (ETR) by comparing the income tax burden with profit before tax. The results obtained from this study are independent commissioners and institutional ownership have no significant effect on tax avoidance, while the audit committee has a significant negative effect on tax avoidance.